2004
DOI: 10.1292/jvms.66.1289
|View full text |Cite
|
Sign up to set email alerts
|

Use of Monoclonal Antibodies for Analyses of Coxiella burnetii Major Antigens

Abstract: Monoclonal antibodies (MAbs) to major antigens of Coxiella burnetii were produced. Some of the MAbs to a 62-kDa protein antigen, peptidoglycan protein complex and lipopolysaccharide (LPS) O-chains reacted with other bacteria whereas none of the MAbs to outer membrane proteins and LPS outer-core did. The LPS outer-core and OMPs may be useful antigens for specifically detecting antibodies to C. burnetii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In most of these articles total protein extracts were analyzed, but few studied bacterial protein fractions enriched for outer membrane proteins (Papadioti et al, 2011;Jiao et al, 2014). These outer membrane proteins were found to be advantageous for the development of new vaccines due to their exposition to host immune cells (Hotta et al, 2004;Papadioti et al, 2011).…”
Section: Selection Of Immunoproteomic Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these articles total protein extracts were analyzed, but few studied bacterial protein fractions enriched for outer membrane proteins (Papadioti et al, 2011;Jiao et al, 2014). These outer membrane proteins were found to be advantageous for the development of new vaccines due to their exposition to host immune cells (Hotta et al, 2004;Papadioti et al, 2011).…”
Section: Selection Of Immunoproteomic Publicationsmentioning
confidence: 99%
“…1). Because some authors have suggested that surface exposition might increase the chance for recognition by immune cells (Hotta et al, 2004;Papadioti et al, 2011), we assumed that outer membrane proteins would dominate. Surprisingly, the majority of the identified proteins are located in the cytoplasm (27%), followed by proteins associated with the inner (8%) or outer membrane (7%).…”
Section: Figmentioning
confidence: 99%
“…Antigenic analysis of F. tularensis as well as other members of the genus is important because Francisella novicida and Francisella philomiragia have biochemical and genetic properties similar to those of F. tularensis (9), although they rarely cause tularemia-like diseases (13,22). Monoclonal antibodies (MAbs) are a useful tool for analyzing the antigenic properties of bacteria (15) Hybridoma clones secreting MAbs (M11D3, M11H7, M13B10, M14B11, M15C6, S11E7, and U22F2) were obtained by the fusion of mouse myeloma cells (P3-X63-Ag8.653) and spleen cells from BALB/c mice, which had been immunized with the formalin-inactivated F. tularensis GIEM Miura (Japanese) strain, the Schu (non-Japanese) strain, or the F. novicida U112 strain, as described elsewhere (14). Characteristics of the MAbs (Table 1) were based on MAbs obtained from hybridoma supernatant or mice ascitic fluids.…”
mentioning
confidence: 99%
“…We decided to focus on outer membrane proteins because they represent important virulence factors and are expected to stimulate specific immune responses. Additionally, their antigenic properties are poorly understood during human C. burnetii infection . Our team analyzed the sarcosyl‐insoluble and thus enriched in outer membrane proteins fraction of the two C. burnetii strains using doubled SDS‐PAGE combined with MS/MS analysis.…”
Section: Comparative Proteomics Studiesmentioning
confidence: 99%